Effects of bentonite heating on U(VI) adsorption. (October 2019) - Fox, Patricia M.; Tinnacher, Ruth M.; Cheshire, Michael C.; Caporuscio, Florie; Carrero, Sergio; Nico, Peter S.
Abstract: Engineered barrier systems designed to isolate high-level radioactive waste utilize bentonite, a montmorillonite-rich material, to restrict contaminant transport due to its low hydraulic conductivity and high adsorption capacity. High temperatures (100–200 °C) near waste canisters resulting from radioactive decay may alter the clay's ability to adsorb contaminants. In this study, we examine U(VI) adsorption onto two different bentonite samples subjected to (1) 18 years of in situ heating during an underground experiment and (2) short-term (7-week), high temperature (300 °C) heating in the laboratory. Results show that U(VI) adsorption was lower for field-heated bentonite located closest to the heater, which experienced temperatures of approximately 95 °C, compared to a control sample, which experienced temperatures of approximately 20 °C, over a range of aqueous chemical conditions. On average, Kd values for U(VI) adsorption were 31% lower for 95 °C heated samples. By contrast, U(VI) adsorption onto intermediate-heated bentonite (50 °C) was indistinguishable from the adsorption onto the cold-zone (20 °C) sample. U(VI) adsorption onto lab-heated bentonite was also lower than onto control bentonite over the pH range 4.5–8.0, with an average decrease in Kd values of 50% after heating. Lower U(VI) adsorption to field-heated bentonite persisted after bentonite was purified to isolate the clay fraction. This allows us to rule out changes in pore-water chemistry or accessory mineral composition as causes of the lower adsorption. No evidence of montmorillonite illitization was observed in the heated samples. While some of the lower U(VI) adsorption in the lab-heated bentonite can be explained by changes in aqueous U(VI) speciation, we propose that lower U(VI) adsorption to field-heated bentonite may be primarily due to changes in the montmorillonite edge structure. The observed changes in U(VI) adsorption to bentonite after heating have implications for U(VI) diffusive transport through engineered barriers and must be considered when designing radioactive waste disposal repositories. Graphical abstract: Image 1 Highlights: Uranium adsorption onto 95 °C field-heated and lab-heated bentonite was lower than onto control samples. Intermediate-heated bentonite (50 °C) showed no change in U(VI) adsorption compared to control samples. On average, Kd values decreased by 31% for field-heated bentonite and 50% for lab-heated bentonite. Lower U adsorption persisted on field-heated samples after purification and isolation of the clay fraction. We propose that heat-induced changes to clay may be due to edge site effects such as SiO2 precipitation.